Statistical analysis of social factors influencing academic performance at the University of Puerto Rico's Business Faculty - Vélez Ramos, Daiver De Jesús; Ayala Godoy, Jairo Arturo; Aparico Cuello, Rafael; Castrillón Velandia, Oscar; Flórez Gómez, Edwin; Vélez Ramos, Daiver De Jesús; Ayala Godoy, Jairo Arturo; Aparico Cuello, Rafael; Castrillón Velandia, Oscar; Flórez Gómez, Edwin (Corporación Universitaria Americana, 2024)
Introduction: The academic preparedness of incomingstudents at the Faculty of Business Administration, University of Puerto Rico Río Piedras Campus, has significantly declined, creating challenges in improving fundamental skills and academic outcomes. Objective: Identify social factors affecting students' development and performance. Methodology: A cross-sectional descriptive and inferential approach was used, examining variables such as residence, school type, and entry scores from 2018-2019 to 2022-2023. Results: Findings reveal that dependency status and prior education quality, whether from public or private schools, notably impact academic success. The study also highlights a consistent decline in academic performance over the past six years. Conclusions: The need for targeted interventions to address social disparities and improve student success is emphasized.